Factors influencing Indonesian women's use of maternal health care services. Issue 1 (2nd January 2018) - Kurniati, Anna; Chen, Ching-Min; Efendi, Ferry; Berliana, Sarni Maniar
ABSTRACT: Employing the 2012 Indonesia Demographic and Health Survey data, we aimed to examine factors influencing married women to use maternity services. Data of married women who had given birth in the last five years before the survey were included in the analysis ( n = 14, 672). Factors of education, employment, women's age at first marriage, age at first birth, spousal education difference, contraceptive use, place of residence, and woman's attitude toward wife beating were associated with the use of antenatal care, institutional delivery, and postnatal care services. The likelihood of women using those recommended maternal health care services increased along with the increased educational attainment among women and their spouses, and the older age at first birth. Higher schooling years may contribute to improving adequate maternal health care. Community awareness on maternal health issues should be promoted and include the prevention of early marriage, teenage pregnancies, and domestic violence.